"Swallow Them All, and It's Just Like Smack": Comorbidity, Polypharmacy, and Imagining Moral Agency alongside Methadone and Antipsychotics (Medicine Anthropology Theory, 2023)
This research article investigates moral agency in the spaces between the methadone clinic and the inpatient psychiatric ward by exploring the ways dually-diagnosed service users move though ever-more labyrinthine networks of care. I ask: how are patients’ own engagements with the ethical stakes of such care both made possible and delimited by virtue of their proximity to substances that are understood to affect their subjectivities, wills, and capacities for self-governance? Drawing on fieldwork in the community mental health network of Dublin, Ireland, and following my interlocutors’ own reflections, I analyse the moral dimensions of polypharmaceutical treatment for substance use disorder in the context of psychiatric dual diagnosis. I illustrate how various apparatuses of coercion and care apprehend and govern patients who are thought to be both addicted and mad, simultaneously enthralled by one form of the pharmakon and dangerously unreasonable when other medications are absent or neglected. In the space of such medicated subjectivities, a curious but ultimately revelatory claim to authority about the intended and unintended effects of polypharmaceutical treatment takes shape.